Post-treatment human papillomavirus antibody kinetics in cervical cancer patients - Piontek, Till; Harmel, Christoph; Pawlita, Michael; Carow, Katrin; Börner, Juliane; Runnebaum, Ingo B.; Dürst, Matthias; Graw, Frederik; Waterboer, Tim (Philosophical transactions of the Royal Society of London. Series B, Biological sciences, 2019)
Antibodies to the E6 and E7 oncoproteins of high-risk human papillomavirus (HPV) types are strongly associated with HPV-driven cancer, while antibodies against the capsid protein L1 are considered cumulative exposure markers. To test the hypothesis that L1 antibody levels are stable over time, whereas E6 and E7 levels undergo decay after cervical cancer (CxCa) treatment, we performed multiplex serology for HPV16 and 18 antigens E6, E7 and L1 in a post-treatment study of 184 patients with invasive CxCa that were characterized with a median follow-up time of 725 days, and 2–12 sera per patient. ...
Online veröffentlicht am 8. April 2019
Gesehen am 14.08.2019